051 Using quality improvement methodology to implement an electronic paediatric early warning system (PEWS) across great ormond street children's hospital (GOSH). (December 2018) - Peters, M; Moore, P
Abstract : Background: PEWS is a score based system designed to identify potential deterioration in children and young people. Nationally, wide variation exists within the predictive performance of PEWS, but it could be argued the implementation of the score is more important than the score itself. GOSH records and monitors its patients' vital signs electronically, via the digital platforms Nervecentre and CareVue. This allows clinicians to identify, escalate and respond to patients at risk of deterioration at an individual, ward and Trust level. However, replacing an Early Warning System (EWS) electronically adds a level of complexity and risk. Slight adjustments can impact the whole system, with issues such as alert fatigue and device availability threatening success. Methods: The decision to initiate a Quality Improvement project to replace the locally developed and unvalidated Children's Early Warning Score (CEWS) with PEWS was supported by national research and data modelling of over 1.7 million GOSH clinical observations. Project phases: Diagnostics to assess readiness for implementation e.g. driver diagrams Test systems built to simulate and agree technical changes Additional changes e.g. Sepsis alerts/triggers, to support implementation. Nursing and Medical training packages Communications e.g. Twitter and SnapComms, Post–implementation changes based on staff feedback Sustainability e.g. EPR integration Results: Clinical Emergency Team measures for cardiac/respiratory arrests, 2222 calls and unplanned ICU transfers – Percentage of complete observations over time, based on an early warning score being produced – Number and type of observations over time (Nervecentre and CareVue) Conclusion: Electronic EWS can give greater visibility to patients at risk of deterioration. However, overlaying a rigorous process is essential to enhance multi-disciplinary team working, communication and confidence in recognising, reporting and making decisions about a child at risk of deterioration.